The Effect of Covert Rehearsal Model Towards Students Pronunciation Ability - Risman, Elvina Wati; Safitri, Loli (Modality Journal: International Journal of Linguistics and Literature, 2022)
This research aims to find the effect of Covert Rehearsal Model  on students’ pronunciation at second grade IPS of MAN 3 Pasaman Barat. The research was conducted at MAN 3 Pasaman Barat because most of the students still experience obstacles in mastering English, especially in pronunciation. Most students find it difficult to pronounce and distinguish the same sounds with different meaning, and the strategies used by the teacher are always the same. In teaching pronunciation, the teacher only asks the students to repeat the spoken word after her. The fact is the students were not provided with the right model. This research uses experimental research. It is a quasi-experimental design by using the  non-equivalent control group. The population of this reseach is 73 students. To  determine the sample, the researcher uses purposive sampling technique. The researcher chose the class XI IPS 1 and XI IPS 3 as the sample of this research. Class XI IPS 1 was treated as Experiment class which was taught by using Covert Rehearsal Model  and XI IPS 3 was treated as Control class which was taught by using conventional techniques. The data get  through pre-test and post-test to experimental and control classes. To analyze the data, the researcher used the normality and homogeneity tests by using SPSS 22 application. To test the hypothesis, the researcher uses t-test formula and consulted the result into a t - table with level of significant α= 0.05. From the result of the pre-test and post-test scores of the experimental class, the results of the t-test (5.283) are higher than the t-table (2.093).  So the alternative Hypothesis  (Ha) was accepted which means that there was a significant effect of using the effect of Covert Rehearsal Model Strategy towards students’ Pronunciation. Then, the final calculation of the two classes: experimental and control classes obtained that the t-count is greater than the t-table (50.75>49.86) so that the alternative hypothesis (Ha) is accepted which means that there is a significant difference between the use of the Covert Rehearsal Model with conventional techniques. Finally, it can be concluded that the Covert Rehearsal Model strategy have a significant effect on students' pronunciation abilities.Peneliti ini bertujuan untuk menemukan pengaruh penggunaan Covert Rehearsal Model terhadap pronunciation siswa kelas XI IPS MAN 3 Pasaman Barat. Penelitian ini dilakukan di MAN 3 Pasaman Barat karena sebagian besar siswa masih mengalami kendala dalam penguasaan Bahasa Inggris terutama pada pronunciation. Sebagian besar  siswa sulit melafalkan dan membedakan bunyi yang sama, dengan perbedaan makna yang sama, dan strategy yang di gunakan guru dalam mengajar selalu sama. Dalam mengajarkan pronunciation, guru hanya meminta siswa mengulang kata yang diucapkan setelahnya. Faktanya siswa tidak diberikan model yang tepat untuk meningkatkan kemampuan pronunciation. Jenis penelitian yang digunakan adalah penelitian eksperimen. Peneliti menggunakan penelitian quasi eksperimen dengan menggunakan model non-equivalent. Populasi dari penelitian ini adalah 73 siswa. Peneliti menggunakan teknik purposive sampel untuk menentukan sampel penelitian ini. Peneliti memilih kelas kelas XI.IPS 1 dan kelas XI.IPS 3 di MAN 3 Pasaman Barat sebagai sample dari penelitian ini. Untuk kelas XI.IPS 3 diperlakukan sebagai kelas eksperimen yang di ajar dengan menggunakan strategi Covert Rehearsal Model. Sedangkan kelas XI. IPS 1 diperlakukan sebagai kelas kontrol yang di ajarkan dengan menggunakan teknik yang biasa. Data diperoleh melalui pre-tes dan post-tes untuk kelas control dan kelas eksperimen. Untuk menganalisis data, peneliti menggunakan tes normalitas dan homogenitas dengan menggunakan aplikasi SPSS 22. Sedangkan untuk menguji hypothesis, peneliti menggunakan uji-t dan mengkonsultasikan hasilnya dengan tabel t untuk hipotesis pertama kedua.Dari hasil perhitungan pre-tes dan post-tes dari kelas eksperimen terdapat hasil uji t-hitung (5,283) lebih tinggi dari pada t-tabel (2,093). Jadi hipotesis alternatif (Ha) diterima yang maknanya bahwa ada pengaruh yang signifikan dengan menggunakan strategi Covert Rehearsal Model. Kemudian, perhitungan akhir dari kedua kelas: kelas eksperimen dan kontrol diperoleh t-hitung lebih besar  dari pada t-tabel (50,75>49,86) sehingga hipotesis alternatif (Ha) diterima yang maknanya bahwa ada perbedaan yang signifikan antara penggunaan strategi Covert Rehearsal Model dengan teknik konvensional. Akhirnya dapat disimpulkan bahwa strategi Covert Rehearsal Model dapat memberikan efek yang signifikan terhadap kemampuan Pronunciation siswa.